Women’s self-reported symptoms of reproductive tract infection, medical consultations, and factors influencing them in less developed regions: perimenopausal and older women in need of urgent attention - Zhang, Ruoyi; Kang, Dan; Yang, Siyuan; Hu, Dehua; Bai, Li; Ao, Yongping; Chen, Jiaojiao; Nie, Yuxian; Zhao, Xiaowei; Xu, Wei; Shi, Qiuling (Frontiers in Public Health, 2024)
Background Reproductive tract infections (RTIs) represent a critical public health concern impacting women’s health, particularly pronounced in developing countries. We aim to investigates the prevalence of self-reported RTI symptoms in women aged 18 to 65 and the factors influencing gynecological examination behavior and associated risks are explored. Methods From May 6, 2022, to September 20, 2022, a comprehensive survey engaged 20,864 women aged 18 to 65 in 19 townships in Lueyang, Shaanxi. Each survey team, comprising a gynecologist, two female health center staff, and a master’s student, conducted face-to-face questionnaire surveys in villages and households. The questionnaire featured three sections: prevalence of self-reported RTI symptoms, gynecological examination history, and factors influencing examination behavior. Results The high response rate of 98.69% yielded 20,590 valid questionnaires. Among surveyed women, 42.04% reported RTI symptoms, with a higher prevalence in those aged 30 and above, peaking at 44.88% in the 50–59 age group. Vulvar itching (24.73%), abnormal vaginal discharge (17.41%), and urinary tract irritation signs (11.73%) were most common. Older adult women (≥60) reported higher frequency and longer duration of symptoms. Only 9.88% of symptomatic women underwent gynecological examinations in 2022. Examination likelihood decreased with age, presenting a critical gap in healthcare utilization among older women. Reasons for checkups included routine checkups (47.02%), symptom concerns (41.29%), and the availability of free medical checkup programs (9.82%). Barriers included perceived lack of serious symptoms (23.7%), lack of necessity (4.41%) and lack of time (3.98%). Among those examined, 40.58% had a diagnosis of gynecological disorders, including pelvic inflammatory disease, human papilloma virus infection and cervical cancer. Conclusion Widespread RTI symptoms, particularly in perimenopausal and older women, underscore the need for enhanced healthcare. Barriers to gynecological examinations include awareness, education, and accessibility issues. Strategies must prioritize health education, routine examinations, and improved healthcare infrastructure in underdeveloped regions.